Effects of Centella Asiatica (L) Urb. on Cognitive Function in Hypothyroid Mice Offspring - Khairinisa, Miski A.; Alfaqeeh, Mohammed; Patricia, Vinda M. (Pharmacology and Clinical Pharmacy Research, 2023)
Centella asiatica (C. asiatica) is widely used in traditional medicine due to its numerous health benefits. Among its reputed advantages are improved memory, intelligence, and neural protection. Impairment of cognitive function as a center for memory processing occurs due to perinatal hypothyroidism. Although several studies have shown that C. asiatica extract may improve memory function, the effectiveness of its extract as a memory enhancer for patients with perinatal hypothyroid is less unknown. Therefore, this study aimed to determine the effects of ethanol extract of C. asiatica (EEC) leaf as a memory enhancer in perinatal hypothyroid mice model. C. asiatica leaves were extracted by the decoction method, and the ethanol extract was administered to mice. the hypothyroid mouse model was developed by administering antithyroid agents to pregnant mice from gestational day (GD) 18 to postnatal day (PND) 21. The hypothyroid mice were administered either donepezil 5 mg/kg BW/mL (positive control) or treatment group (EEC 2 mg/kg BW/mL) from PND 21 to PND 35 (14 days). The light-dark test (LDT) and memory tests of offspring were conducted on PND 36. We found that EEC improved the cognition and memory of perinatal hypothyroidism mice. This study contributes to the foundational research for developing memory-enhancing supplement preparations, mainly targeting children with perinatal hypothyroidism.